Nilai Pendidikan Karakter dalam Novel Tuhan Mengapa Kau Memberiku Wajah Ini? Karya Isa Alamsyah - Kuntum Khairul Ummah; Rahayu, Sri (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
This research is motivated by the lack of development of basic potential in humans to become individuals who think and behave well, especially for students in the field of education. By using a qualitative approach and descriptive methods, this research data is in the form of clauses, sentences and paragraphs which contain educational value obtained from the novel “Tuhan Mengapa Kau Memberiku Wajah Ini?” by Isa Alamsyah. The data collection technique in this research uses hermeneutic techniques. The results of the research show that there are educational values in the form of aspects of faith and devotion, aspects of caring, aspects of intelligence, and aspects of toughness. This research can be used to enrich the reading experience and model character education for students.